A passive house with photovoltaic, heat pump, and Stirling engine. : An energy-balance model - Virtanen, Eero (My University, 2024)
The purpose of this thesis is to analyse a way of heating a passive house with a thermal energy source instead of electricity, while still taking advantage of the high coefficients of performance typical for heat pumps. To achieve this, a thermal energy balance model of a passive house with photovoltaic electricity generation, a heat pump for temperature control and a Stirling engine to directly power the heat pump is created. The thesis will focus only on the heating, but not the cooling of a passive house and therefore example calculations are made for a cold climate. The thesis was heavily inspired by “CO2 Stirling Heat Pump for Residential Use” (2008) by M. Berchowitz et al. From the analysis it is found that even in a non-optimal configuration in a cold climate, the heating system achieves an average coefficient of performance of almost 2. Therefore, the addition of a Stirling engine heat pump should be able to halve the amount of fuel needed for heating and has potential for even better numbers. The performance is based on the usage of an air-source heat pump to transfer heat. A notable improvement is achievable by changing over to a ground-source solution. Even though there are significant shortcomings in the mathematical model, rough energy consumption numbers are calculated. They show that the solution presented should be able to satisfy most if not all the requirements of the passive house standard. The model is also clearly divided into heats produced by different phenomena, making it easy to improve upon in the future. The accuracy of used equations is analysed qualitatively.

Tämän tutkielman tarkoitus on luoda energiatasapainomalli, joka kuvaa passivitalon lämmittämistä lämpöenergian lähteellä sähköenergian sijaan. Tämän mahdollistaa passiivitalo, jossa on aurinkopaneelit ja suoraan lämpöpumppuun mekaanisesti kytketty Stirling-moottori. Tällöin on mahdollista hyötyä lämpöpumppujen korkeista suorituskertoimista myös käytettäessä lämpöenergiaa. Tutkielma keskittyy vain passiivitalon lämmitykseen, mutta ei jäähdytykseen, ja esimerkkilaskelmat tehdään kylmässä ilmastossa sijaitsevalle talolle. Tutkielma sai paljon inspiraatiota teoksesta "CO2 Stirling Heat Pump for Residential Use" (2008) tekijöinään M. Berchowitz ym. Analyysistä käy ilmi, että jopa ei-optimaalisessa konfiguraatiossa lämmitysjärjestelmä saavuttaa keskimääräisen suorituskertoimen, jonka arvo on lähes kaksi. Täten Stirling-lämpöpumppuyhdistelmän lsääminen tulisi vähentämään lämmitykseen tarvittavan polttoaineen määrää vähintään puolella, joskin mahdollisuus parempiinkin lukemiin on olemassa. Merkittävä parannus tässä tutkielmassa esiteltyyn esimerkkiin on saavutettavissa siirtymällä ilmalämpöpumpusta maalämpöratkaisuun. Vaikka matemaattisessa mallissa on merkittäviä puutteita, esimerkkitalolle saadaan karkeat energiankulutusta kuvaavat luvut. Ne osoittavat, että esitelty ratkaisu voisi tyydyttää suurimman osan elli jopa kaikki passiivitalostandardin vaatimuksista. Matemaattinen malli on jaettu selvästi eri ilmiöhin ja niiden vaikutuksiin, jotta sen muokkaaminen tarkkuuden parantamiseksi olisi helpompaa. Käytettyjen yhtälöiden tarkkuutta arvioidaan laadullisesti.
Keywords: passive house, Stirling engine, residential heating, free piston Stirling engine, free piston Stirling engine heat pump